Pengaruh Metode Amtsilati Terhadap Kemampuan Membaca Kitab Kuning Santri - Al Ghozali, M. Dzikrul Hakim; Diva, Melvina Diva Labibah (Qismul Arab: Journal of Arabic Education, 2023)
This study aims to determine the application of the amtsilati method in PP. As-Sa'idiyyah 1, and to determine the effect of the amtsilati method on the ability to read the yellow book of PP students. As-Sa'idiyyah 1 Bahrul 'Ulum Tambakberas Jombang. The problem of this research started with the students who had difficulty understanding the grammatical Arabic, nahwu and shorof for learning the yellow book. This research uses quantitative research methods. where the research instrument used was a questionnaire using a Likert measurement scale. The population in this study amounted to 60 respondents. The data analysis technique uses a simple linear regression test and is proven using the partial t test. The level used is 0.05. The results of this study indicate that there is an effect of the amtsilati method on the ability to read the yellow book of PP students. As-Sa'idiyyah 1 Bahrul 'Ulum of Jombang rice ponds. This is proven by using the partial t test, namely 0.000 <0.05, which means that Ho is rejected and Ha is accepted. Thus that there is an influence of the amtsilati method on the ability to read the yellow book of students.